Presidential and Media Leadership of Public Opinion on Iraq1. Issue 4 (2nd May 2013) - Eshbaugh‐Soha, Matthew; Linebarger, Christopher
Abstract : Much research disputes the president's ability to lead public opinion and shows media to have influenced public opinion concerning the war in Iraq. We argue that although news tone is likely to have affected public support for the war, presidential rhetoric could be influential for two reasons. First, heightened presidential attention to the war increases the public's accessibility to the president's perspective on the war. Second, a survey question that cues the respondent to consider the president explicitly in their evaluation of the Iraq war is likely to encourage responsiveness to presidential rhetoric. To assess these arguments, we simultaneously examine the impact that presidential tone and media tone have on public support for the war in Iraq by analyzing an original dataset of presidential speeches, news coverage, and public support for the war and the president's handling of it from 2002 to 2008. Our findings reveal that although media tone drives public support for the war in Iraq, presidential tone influences the public's view of President Bush's handling of it.